Diana: princess of the Amazons - Hale, Shannon; Hale, Dean, 1972-; Ying, Victoria; Marston, William Moulton, 1893-1947 (Burbank, CA : DC Comics, 2020)
Eleven-year-old Diana, the gangly, sometimes clumsy, only child on the island of Themyscira, struggles to live up to the high Amazonian standards and longs for someone her own age whom she can talk to.
School Library Journal, November 2019
Publishers Weekly, October 2019
Kirkus Review, November 2019
4.2
3-6
Keywords: Wonder Woman -- (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Self-esteem -- Comic books, strips, etc. -- Juvenile fiction; Superheroes -- Comic books, strips, etc -- Juvenile fiction; Fantasy comic books, strips, etc; Wonder Woman -- (Fictitious character) -- Fiction; Loneliness -- Fiction; Self-esteem -- Fiction; Amazons -- Fiction; Superheroes -- Fiction; Fantasy; Cartoons and comics; Superhero comics; Fantasy comics; Graphic novels